PERSEPSI MAHASISWA JURUSAN TEKNIK SIPIL FT-UNP TERHADAP PELAKSANAA PERKULIAHAN GAMBAR TEKNIK SECARA DARING ERA PANDEMI COVID-19 - Miftahul Rahmi Yati; Revian Body (Jurnal Applied Science in Civil Engineering, 2021)
Abstract: This study aims to illustrate students' perception of online lectures in Gambar Tekni courses which are reviewed from the role of lecturers as facilitators and the availability of facilities and infrastructure. This research includes the type of survey research. The population in this study were students who attended the Technical Drawings lecture in the semester period July-December 2020. The population was 204, and the sample was 51. Sampling using simple random sampling techniques, the number of samples determined 25% of the population. The variables studied are only one variable. The research instruments used are questionnaires. The number of statements on the questionnaire is 13 points. Before the data collection, validation was carried out on validator lecturers and trials to 30 students. This is done to find out if the instrument is valid and reliabel. The data is analyzed manually, using Microsoft Office Excel 2010 programs and spss statistic 17.0. The percentage of perception of FT-UNP Civil Engineering Students towards the implementation of Online Engineering Drawing lectures during the covid-19 pandemic period in the semester of July-December 2020 is in the good category (84.65 %). Seen in the indicators of the role of lecturers perception of students is quite good (88.2 %), as well as in the indicators of facilities and infrastructure is in the good category (81.7 %).